Comparing postural balance among older adults and Parkinson's disease patients - Isabela Andrelino de Almeida; Marcelle Brandão Terra; Marcio Rogério de Oliveira; Rubens Alexandre da Silva Júnior; Henrique Ballalai Ferraz; Suhaila Mahmoud Smaili Santos
ABSTRACT The objective of this study was to compare postural balance among healthy older adults and Parkinson's disease (PD) patients during one-legged stance balance. We recruited 36 individuals of both sexes and divided them into two groups: healthy older adults (HG), and individuals with PD (PG). All the participants were assessed through a single-leg balance test, with eyes open, during 30 seconds (30 seconds of rest across trials) on a force platform. Balance parameters were computed from mean across trials to quantify postural control: center of pressure (COP) area and mean velocity in both directions of movement, anterior-posterior and medial-lateral. Significant differences between-group were reported for area of COP (P=0.002) and mean velocity in anterior-posterior direction (P=0.037), where poor postural control was related to PD patients rather than to healthy individuals. One-legged stance balance was a sensitive task used to discriminate poor postural control in Parkinson individuals.